2013
DOI: 10.1128/mcb.00198-13
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast AMPK Homolog SNF1 Regulates Acetyl Coenzyme A Homeostasis and Histone Acetylation

Abstract: Acetyl coenzyme A (acetyl-CoA) is a key metabolite at the crossroads of metabolism, signaling, chromatin structure, and transcription. Concentration of acetyl-CoA affects histone acetylation and links intermediary metabolism and transcriptional regulation. Here we show that SNF1, the budding yeast ortholog of the mammalian AMP-activated protein kinase (AMPK), plays a role in the regulation of acetyl-CoA homeostasis and global histone acetylation. SNF1 phosphorylates and inhibits acetyl-CoA carboxylase, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 78 publications
(130 reference statements)
4
68
0
Order By: Relevance
“…Studies in yeast showed that increased availability of AcCoA due to Acc1 gene deletion was sufficient to enhance histone acetylation (13,45). Similarly, activation of ACC1 by inhibition of AMPK in yeast resulted in decreased histone acetylation (44). In budding yeast, AcCoA production by the PDC in the mitochondria was indirectly altered by deletion of mitochondrial pyruvate carrier-1 (MPC1), resulting in accumulation of acetate in the cytosol, triggering upregulation of the cytosolic AceCS1 for AcCoA production, increased histone acetylation, and repression of autophagy genes (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast showed that increased availability of AcCoA due to Acc1 gene deletion was sufficient to enhance histone acetylation (13,45). Similarly, activation of ACC1 by inhibition of AMPK in yeast resulted in decreased histone acetylation (44). In budding yeast, AcCoA production by the PDC in the mitochondria was indirectly altered by deletion of mitochondrial pyruvate carrier-1 (MPC1), resulting in accumulation of acetate in the cytosol, triggering upregulation of the cytosolic AceCS1 for AcCoA production, increased histone acetylation, and repression of autophagy genes (10).…”
Section: Discussionmentioning
confidence: 99%
“…Denatured proteins were separated on a 15% denaturing polyacrylamide gel. Western blotting with anti-histone H3 polyclonal antibody (catalog number ab1791; Abcam) at a dilution of 1:1,000, anti-histone H4 polyclonal antibody (catalog number 2542; Cell Signaling) at a dilution of 1:750, anti-histone H2A polyclonal antibody (catalog number 07-146; Millipore) at a dilution of 1:750, and anti-histone H2B polyclonal antibody (catalog number 07-371; Millipore) at a dilution of 1:750 was carried out as described previously (43,44). To confirm equivalent amounts of loaded proteins, the membranes were also probed with actin polyclonal antibody (catalog number A5060; Sigma) at a dilution of 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…The pools of acetyl-CoA in the nucleocytosolic and mitochondrial compartments are separate; the concentration of acetyl-CoA in the nucleocytosolic compartment affects protein acetylation in the nucleus and cytosol (10,45,106), while the concentration of acetyl-CoA in mitochondrion affects acetylation of mitochondrial proteins (13). In cells exponentially growing on glucose, the mitochondrial pool of acetyl-CoA represents about 30% of the total cellular pool (13).…”
Section: Regulation Of Acetyl-coa Homeostasismentioning
confidence: 99%
“…The first and rate-limiting reaction in de novo synthesis of fatty acids is carboxylation of acetyl-CoA to form malonyl-CoA, a reaction that is catalyzed by acetyl-CoA carboxylase (Acc1p) (120). Decreased flux of acetyl-CoA through the fatty acid synthesis pathway by reducing ACC1 expression results in an increased cellular level of acetyl-CoA, globally increased histone acetylation, and altered transcriptional regulation (45,106). It is interesting that hypomorphic ACC1 mutations were isolated in a genetic screen for suppressors of inositol auxotrophy caused by low expression of the INO1 gene in snf1⌬ cells (122).…”
Section: Regulation Of Acetyl-coa Homeostasismentioning
confidence: 99%
See 1 more Smart Citation